Endovascular Treatment of Complicated Popliteal Aneurysms Using the Novel “Trap and Fix” Technique - Zola N’Dandu, MD; Khaldia Khaled, MD; Richard Ayetevi Agbodji, MD; Georgios Papapostolou, MD; Andrej Schmidt, MD; Grigorios Korosoglou, MD (JACC: Case Reports, 2023)
Herein, we present 2 patients with lower limb ischemia caused by complicated popliteal aneurysms with thrombosis and distal embolization, compromising blood flow to the foot. In both cases, covered stents were first implanted guided by intravascular ultrasound and computed tomography angiography, respectively. After “trapping” the thrombi, mechanical thrombectomy or further stent implantations were performed, “fixing” the remaining lesions and preventing embolization. (Level of Difficulty: Intermediate.)